Dampak K-Pop terhadap Perilaku Fanatisme pada Remaja Masa Akhir di Era Globalisasi di Desa Sumurber Panceng Gresik - Mustahliyatul Hakimah; Ahmad Maujuhan Syah (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
Along with the development of technology in this globalization era, it is very easy for humans to obtain information, one of which is getting information with access to the development of the k-pop world. The easier it is to get this information, it causes teenagers to become fanatical about their idols. As a result of the adolescent fanaticism, it causes the impact and attitudes of adolescent behavior. The causes are from drama series, music, fashion, artists, social media. No wonder if watching k-pop will have an impact and behavior on teenagers. The formulation of the problem in this study is how the impact of k-pop on adolescent fanatic behavior and how the attitude of fanatical behavior in adolescents. The purpose of this study is to determine the impact of k-pop on adolescent fanatic behavior and to determine the attitude of fanatical behavior in adolescents. The research method uses a design with a qualitative approach and the type of research is a case study. The data collection procedure used is interviews. Checking the validity of the data carried out is observation and triangulation. The results showed that the subject had the same k-pop impact that was felt by each subject, some were the same and some were different and had gone through the same and different behavioral attitudes according to the intensity, values ​​and attitudes, commitment of each subject.